Design modern structure for heterojunction quantum dot solar cells - A. Thabet; S. Abdelhady; Youssef Mobarak (International Journal of Electrical and Computer Engineering (IJECE), 2020)
This paper proposal new structure for improving the optical, electrical characteristics and efficiency of 3rd generation heterojunction quantum dot solar cell (HJQDSC) (ITO/CdS/QDPbS/Au) model by using the quantum dot window layer instead of bulk structure layers cell. Also, this paper presents theoretically analysis for the performance of the proposal HJQDSC (ITO/QDCdS/QDPbS/Au) structure. The new design structure was applied on traditional (SnO2/CdS/CdTe/Cu) and (ZnO/CdS/CIGS/Mo) thin film solar cells which based on sub-micro absorber layer thickness models by replacing the bulk CdTe, CIGS absorber layers and CdS window layer with quantum dot size materials to achieve higher efficiency with lesser usage layer material. Also, it has been studied the effect of using semiconductors layers in quantum dots size on electric and optical properties of thin film solar cells and the effect of window and absorber layers quantum dots radii on the performance of solar cells. Finally, a thermal efficiency analysis has been investigated for explaining the importance of new structure HJQD solar cells.